2016
DOI: 10.1152/ajpgi.00350.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofN-glycosylation on the transport activity of the peptide transporter PEPT1

Abstract: The intestinal peptide transporter PEPT1 provides bulk quantities of amino acids to epithelial cells. PEPT1 is a high-capacity and low-affinity solute carrier of the SLC15 family found in apical membranes of enterocytes in small intestine and distal colon. Surprisingly, murine PEPT1 (mPEPT1) has an apparent molecular mass of ∼95 kDa in the small intestine but ∼105 kDa in the large intestine. Here we describe studies on mPEPT1 protein glycosylation and how glycans affect transport function. Putative N-glycosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…In intestinal tissues, murine PEPT1 (mPept1) was demonstrated to be N -glycosylated by predominantly complex-type glycans, which contributed to nearly 1/3 of the protein’s overall apparent molecular weight of ~95 kDa. In contrast to the small intestine, colonic mPept1 was observed to be ~105 kDa, whereas kidney mPept1 was ~75 kDa (56, 59). Using site-directed mutagenesis and protein expression in Xenopus laevis oocytes, six putative glycosylation sites were kinetically characterized, and N50 was identified as a critical residue for the efficiency of peptide transport.…”
Section: N-glycosylationmentioning
confidence: 82%
See 1 more Smart Citation
“…In intestinal tissues, murine PEPT1 (mPept1) was demonstrated to be N -glycosylated by predominantly complex-type glycans, which contributed to nearly 1/3 of the protein’s overall apparent molecular weight of ~95 kDa. In contrast to the small intestine, colonic mPept1 was observed to be ~105 kDa, whereas kidney mPept1 was ~75 kDa (56, 59). Using site-directed mutagenesis and protein expression in Xenopus laevis oocytes, six putative glycosylation sites were kinetically characterized, and N50 was identified as a critical residue for the efficiency of peptide transport.…”
Section: N-glycosylationmentioning
confidence: 82%
“…N50 lies close to the membrane surface in extracellular loop 1 (EL1) and when glycosylated is hypothesized to have a negative steric effect on both the substrate binding-site and on the transport mechanism. Therefore, it is expected that deglycosylation at this residue, or alterations in the glycosylation pattern, will positively modulate PEPT1 function (56). However, further investigation suggested that the fundamental role of N -glycosylation at N50 is to protect the extracellular loops from protease degradation in oocytes, and further studies are needed to determine whether this mechanism is consistent in other expression models (57).…”
Section: N-glycosylationmentioning
confidence: 99%
“…This is similar to some other glycoproteins with a transporter function, for example ASCT2, where only membrane trafficking and not the transport function is affected when glycosylation sites are mutated [ 22 ]. In contrast, for other transporters, for example PEPT1 N-linked glycosylation does not affect plasma membrane abundance in Xenopus laevis oocytes, but transport kinetics are lower in the unglycosylated mutant [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the case of P‐gp, non‐glycosylated protein is known to be ubiquitinated and undergo proteasomal degradation. Contrarily, both glycosylation inhibitor and the mutation at the glycosylation site failed to affect the expression of Pept1 in a Xenopus oocyte preparation (Stelzl et al, ). Therefore, the impact of glycosylation may differ between P‐gp and Pept1.…”
Section: Discussionmentioning
confidence: 99%
“…Among the post‐translational modulation processes, N ‐glycosylation plays an important role in the membrane expression of P‐gp and BCRP. It was reported that the protein expression of P‐gp and BCRP was reduced by glycosylation inhibitors or the substitution of asparagine residues, a site of N ‐glycosylation (Bentley, Quinn, Pitman, Warr, & Kellett, ; Hou et al, ; Nakagawa et al, ; Schinkel, Kemp, Dollé, Rudenko, & Wagenaar, ; Sereš, Cholujová, Bubenčíkova, Breier, & Sulová, ; Zhang, Wu, Hait, & Yang, ), while the expression of PEPT1 was not affected by the substitution of asparagine residues (Stelzl, Baranov, Geillinger, Kottra, & Daniel, ). However, the influence of increased glycosylation on the expression level of these transporters remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%